Environment - Hassenzahl, David M (New jersey : John Wiley, 2018)
Environment, Tenth Edition helps students understand the connection between the core concepts of the Environmental Science and their daily lives. The 10th edition enhanced e-text features a rich, interactive collection of current case studies and in-text examples, which provides students with the tools to understand, apply, and think critically about environmental science. It also provides instructors with powerful tools to assess individual students progresses well as the class as a whole.
Includes appendix and index.
Keywords: Environmental science; Climate change; Land Resources; Air Pollution